Alcohol use and strenuous physical activity in college students: A longitudinal test of 2 explanatory models of health behavior. Issue 2 (17th February 2017) - Davis, Heather A.; Riley, Elizabeth N.; Smith, Gregory T.; Milich, Richard; Burris, Jessica L.
ABSTRACT: Objective : To help clarify the effect of gender on the bidirectional relationship between alcohol use and strenuous physical activity in college students.Participants : Five hundred twenty-four (52% female) college students recruited in August 2008 and 2009 and followed up in April 2009 and April 2011, respectively.Methods : Participants reported their alcohol use and strenuous physical activity on 2 occasions (baseline and follow-up) spaced approximately 1 or 2 years apart.Results : For females, alcohol use quantity at baseline was associated with increased strenuous physical activity at 1- and 2-year follow-ups, and alcohol use frequency at baseline was associated with decreased strenuous physical activity at 2-year follow-up. For males, alcohol use frequency at baseline predicted decreased strenuous physical activity at 1-year follow-up.Conclusions : Gender differences may be explained from an eating disorders perspective such that women use physical activity as a compensatory strategy to combat potential weight gain from calories consumed during alcohol use.